Uncanny Valley of Life - The Existence in 3D Animation in Shadow Puppets Theatre - Abdul Ghani, Dahlan (Journal of Computing Technologies and Creative Content, 2016)
Mori (1970) proposed a theoretical graph describing a nonlinear relation between a character’s degree of human likeness and the emotional response of the human perceiver. With the current scenario that Wayang Kulit or shadow puppets is slowly being extinct; the pursuit of realism in virtual humans including Wayang Kulit 3D puppets can cause a phenomenon known as The “Uncanny Valley”. Furthermore, 3D computer animated or virtual puppets are more focused on issues pertaining to realism compared to the abstract visual such as Wayang Kulit itself. Therefore, this research will discuss on issues which arises in the Uncanny Valley of Life that exists especially with Wayang Kulit 3D computer animated puppet characters.